Sistem E-Document dan E-Meeting Sebagai Manajemen Pengetahuan untuk Menuju Tata Kelola Yang Baik Pada Universitas Pembangunan Jaya - Chaerul Anwar; Safitri Jaya; Prio Handoko; Marcello Singadji (Systemic: Information System and Informatics Journal, 2019)
The Knowledge in a study program or faculty at Higher Education is an asset that must be utilized by universities. Explicit knowledge can be in the form of meeting attendance, meeting schedules, minutes of meetings, teaching materials, documentation of the final session, letters (SK, ST, contract letters, etc.), certificates, reports, guidelines, manuals , memos, strategic plans, curriculum and so on. However, knowledge cannot be easily accessed by cross study programs or cross faculties at the college. Some study programs have done documentation so well that it has an impact on satisfying accreditation assessments. Study programs that have satisfactory accreditation can be an example for other study programs. A knowledge management system is needed to bridge the distance between study programs that have good governance and others. The results of the knowledge management system testing allow for the exchange of knowledge to become a means of improving the quality of governance both at the study program level and at the faculty level.